Adhesion durability of dual-cure resin cements and acid–base resistant zone formation on human dentin. Issue 7 (July 2019) - Aung, San San May Phyo; Takagaki, Tomohiro; Ko, Aye Ko; Halabi, Somayah; Sato, Takaaki; Ikeda, Masaomi; Nikaido, Toru; Burrow, Michael F.; Tagami, Junji
Highlights: The cement systems used influenced the morphology of acid–base resistance zone. The self-etch adhesives combined with the cement systems affected the bond strength. The tested cement systems differed in resistance to hydrothermal stress. Abstract: Objectives: Bond durability and resistance to acid-base challenge of dentin with dual-cure resin cement have been rarely investigated. The purpose of this study was to evaluate dentin bond strength and observe the adhesive-dentin interface after acid-base challenge using three different dual-cure resin cements. Methods: Thirty dentin surfaces from caries-free human premolars were ground and bonded with one of three dual-cure resin cements: PANAVIA V5 (V5), ESTECEM II (E II) and Rely X Ultimate (RXU) and thermocycled for 0, 5, 000 and 10, 000 cycles. A microtensile bond strength ( μ TBS) test was undertaken and the interface of the bonded specimens after acid-base challenge was examined by SEM. Results: The μTBS of V5 exhibited a stable bond strength despite thermal cycling while the bond of EII and RXU after 10, 000 cycles dropped significantly among all thermal cycle periods ( p <0.05). An acid-base resistant zone (ABRZ) was observed in all groups, however, the morphology of the bonded interface differed among the tested cements. Conclusion: Bonding durability to dentin and ABRZ morphologies differed among the cements evaluated. PANAVIA V5 cement system with tooth primer provided the most reliable bond strength and was best able to resist the acid–base challenge.